How do the methodological strategies influence the communicative method in the process of teaching-learning of the english language in children of first grade at Centro Educativo Belen Elementary School,Bugaba's District, 2009? - Pitty A., Doris; Méndez C., Yaniris (David, Panamá : UDELAS, 2010)
Through the history pedagogical precursors have been several studies about development of teaching and learning process. Psychologists as Piaget, Bandura, Ausubel and others designed strategic models that became methodological steps used by teachers to transmit knowledge to the students.
TABLE CONTENT 1.1. Background on f the problem Chapter II Theoretical framework 2.1. Historical summary of Belen Community 2.2. History of the Belen school 2.3. Methodological strategies 2.3.1. Concept of method 2.3.2. Definition of technique 2.3.4. Teaching technique 2.3.5. Didactic method 2.4. The method in a general way 2.4.1. Methods of trasnmission 2.5. Classification in the teaching methods And others more Chapter III Methodological framework Chapter IV Investigation results Chapter V Proposal Chapter VI Conclusion and recommendation Chapter VII Bibliography Annex
Incluye Table content
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- TEACHING; FACULTAD DE EDUCACIÓN SOCIAL; DEPARTAMENTO DE INGLÉS; LICENCIATURA EN DOCENCIA EN INGLÉS; BELEN ELEMENTARY SCHOOL, BUGABA - CHIRIQUÍ